Renal effects of angiotensin II receptor subtype 1 and 2-selective ligands injected into the paraventricular nucleus of conscious rats - Camargo, Luiz Antonio de Arruda [UNESP]; Saad, Wilson Abrão [UNESP] (Elsevier, 1999)
We determined the effects of losartan and CGP42112A (selective ligands of the AT1 and AT2 angiotensin receptors, respectively) and salarasin (a relatively nonselective angiotensin receptor antagonist) on urinary volume and urinary sodium and potassium excretion induced by administration of angiotensin II (ANG II) into the paraventricular nucleus (PVN) of conscious rats. Both the AT1 and AT2 ligands and salarasin administered in the presence of ANG II elicited a concentration-dependent inhibition of urine excretion, but losartan inhibited only 75% of this response. The IC50 for salarasin, CGP42112A, and losartan was 0.01, 0.05, and 6 nM, respectively. Previous treatment with saralasin, CGP42112A and losartan competitively antagonized the natriuretic responses to PVN administration of ANG II, and the IC50 values were 0.09, 0.48, and 10 nM, respectively. The maximum response to losartan was 65% of that obtained with saralasin. Pretreatment with saralasin, losartan, and CGP42112A injected into the PVN caused shifts to the right of the concentration-response curves, but the losartan concentrations were disproportionately greater compared with salarasin or CGP42112A. The IC50 values were 0.06, 0.5, and 7.0 for salarasin, CGP42112A, and losartan, respectively. These results suggest that both AT1 and AT2 receptor subtypes in the PVN are involved in ANG II-related urine, sodium, and potassium excretion, and that the inhibitory responses to AT2 blockade are predominant. Copyright (C) 1999 Elsevier Science B.V.
Keywords: AT1 receptors; AT2 receptors; Diuresis; Kaliuresis; Natriuresis; PVN; angiotensin receptor; ligand; losartan; nicotinoyltyrosyl(n benzyloxycarbonylarginyl)lysylhistidylprolylisoleucine; animal experiment; animal tissue; histology; homeostasis; intracerebral drug administration; kaliuresis; male; natriuresis; nonhuman; priority journal; rat; thalamus midline nucleus; urinalysis; Angiotensin II; Animals; Injections, Intraventricular; Kidney; Ligands; Losartan; Male; Oligopeptides; Paraventricular Hypothalamic Nucleus; Potassium; Rats; Rats, Sprague-Dawley; Receptors, Angiotensin; Saralasin; Sodium